OC2 The Soluble Il-6 Receptor Is Related To Weekly Training Volume And Fatigue In Highly Trained Swimmers. (21st October 2014) - Cullen, T; Thomas, AW; Webb, R; Phillips, T; Hughes, MG
Abstract : Interluekin-6 (IL-6) plays an important role in immunological, inflammatory and metabolic responses to exercise. The downstream effects of IL-6 signalling are dependent on the binding to its receptors, both soluble (sIL-6R) and membrane bound. There is evidence that sIL-6R concentrations change in response to exercise and are related to exercise load and fatigue. However, considerably less is known about the sIL-6R response to prolonged exercise training. Knowledge of the receptor response to training may provide insight into the mechanisms underlying cytokine regulation of a number of biological processes. This study investigated the effect of a prolonged period of training on sIL-6R and how this related to perceptions of fatigue. Ten (7 females, 3 males) highly trained swimmers participated. sIL-6R was determined from capillary blood samples collected prior to training each week for a period of 18 weeks. Participants also completed a subjective wellbeing-monitoring questionnaire once a week prior to training. sIL-6R was negatively correlated to weekly training volume (r = -0.68, r 2 = 0.47, p < 0.005). sIL-6R was 74% higher (25.7 Vs 14.8 ng/ml, p = 0.04) in those reporting lowest Vs highest ratings of fatigue. This study provides a) further evidence for the role of the sIL-6R in sensations of fatigue at rest and b) novel evidence that the sIL-6R is responsive to long-term endurance training and that this response is associated with training volume. sIL-6R appears to be responsive to weekly training mileage, decreasing during periods of increased training mileage and returning to baseline levels when training mileage is reduced. Given that IL-6 in combination with sIL-6R is reported to have a greater sensitising effect with regard to nociception/inflammatory hyperalgesia than IL-6 alone, the observed decline in circulating sIL-6R may provide a mechanism for the impact of exercise on perceptions of fatigue, and hence the ability to adhere to high-mileage training.